Business Dispute Resolution: Insight from Indonesia and Saudi Arabia - Atty Genald Malvas Valones; Daniel Krisnugrahanto; Malik Al Farabi (Journal of Private and Commercial Law, 2023)
In legal disputes, the crucial aspect lies in the execution of a decision. A decision holds no value if it cannot be effectively enforced, even if it possesses permanent legal force. To settle civil cases, two prominent institutions are employed: the court and arbitration. In the context of international business agreements, parties turn to international arbitration as a means of resolving disputes, employing neutral third parties. This paper delves into the process of international arbitration, particularly focusing on its application within the business sector. Various arbitration clauses in international business agreements establish international arbitration, with the objective of impartially addressing disputes between parties involved. A notable institution that facilitates such resolution is the Saudi Center for Commercial Arbitration (SCCA) in Saudi Arabia. However, the effectiveness of arbitration rests on the implementation of arbitration awards, which is influenced by the type of arbitration undertaken, whether national or international. Hence, this paper aims to draw a comparative analysis between the Indonesian National Arbitration Board (BANI) and the Saudi Center for Commercial Arbitration (SCCA), examining the legal basis employed and the processes involved in resolving arbitration disputes. By understanding the contrasting practices of these arbitration institutions, stakeholders can gain insights into optimizing dispute resolution mechanisms. The study holds practical significance for businesses and individuals engaged in international trade, emphasizing the importance of selecting the appropriate arbitration institution to ensure enforceability and expeditious resolution of disputes. Ultimately, the findings of this research contribute to fostering a more efficient and reliable international arbitration framework.